Penelope Writes Back: A Poetics of The Penelopiad - Ahmed, Shokhan Rasool; Salih, Hersh Mohammed Saeed (Sulaimani Journal for Humanities, 2022)
This paper is an extract from an MA thesis which is entitled “Deconstructing the Classical Myths: A Postmodern Study of Atwood’s The Penelopiad and Toibin’s House of Names”. The paper studies Margaret Atwood’s The Penelopiad – a contemporary rewriting of Homer’s The Odyssey – according to a poetics of postmodernism. The novella’s literary style, the paper proposes, can be aptly interpreted through the techniques of: polyphony, metafiction, and intertextuality. These narrative techniques are corresponding to postmodernity’s condition of knowledge which is characterized by little narratives (relativism), plurality of discourses (multiperspectivity), and deconstructing any grand narratives, such as mythical, religious or scientific narrations (demythologization). Thus, upon deconstructing The Odyssey’s mythical stories, The Penelopiad constructs a contemporary mythopoeia.
Keywords: Deconstruction; Mythopoeia; Polyphony; Metafiction; and Intertextuality